2002
DOI: 10.1017/s0022112002008224
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surfactant on the stability of a liquid thread

Abstract: The surface-tension-driven motion of a surfactant-coated liquid thread in inviscid surroundings is investigated using linear stability theory as well as one-dimensional nonlinear approximations to the governing Navier–Stokes equations. Examination of analytic limits of the linear dispersion relationship demonstrates that surfactant acts as a distinct mechanism for long-wavelength cut-off, instead of inertia, if the surfactant effects exceed a critical value, β = ½, where β is a dimensionless surface-tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 25 publications
3
131
2
Order By: Relevance
“…It is worthwhile noting that, in disagreement with recent theoretical predictions (Timmermans & Lister 2002), albeit for insoluble surfactants, the final interfacial tension is not that of pure water. In principle, it remains possible that there is an ultimate state of breakup in which the surface is completely devoid of surfactants.…”
Section: Inertial Casecontrasting
confidence: 69%
See 2 more Smart Citations
“…It is worthwhile noting that, in disagreement with recent theoretical predictions (Timmermans & Lister 2002), albeit for insoluble surfactants, the final interfacial tension is not that of pure water. In principle, it remains possible that there is an ultimate state of breakup in which the surface is completely devoid of surfactants.…”
Section: Inertial Casecontrasting
confidence: 69%
“…Theoretical work on drop formation with insoluble surfactants suggests that the ultimate stages of the thinning of the fluid neck just before breakup may be accompanied by a total depletion of the surfactants from the rupture zone leaving the surface bare, i.e. without surfactant (Timmermans & Lister 2002). That the surfactant is depleted significantly from the rupture zone, engendering large gradients of the surface concentration of the surfactant has been confirmed by numerical work for both soluble (Craster et al 2009) and insoluble surfactants (Craster et al 2002;Xu et al 2007).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…To discuss the general linear stability properties we note that in the absence of electric fields, the core thread is subject to Rayleigh instability when the wavenumber of the perturbation is below the critical value k = 1. The presence of the annular fluid provides a long wavelength cut-off with the growth rate becoming zero at k = 0 as opposed to the constant value predicted by Stokes flow (see Timmermans & Lister (2002) for a discussion of this and several other limits in the linear regime). Such effects are shown in figure 2 when an electric field is also present; the dotted lines in panels (a) and (b) represent the results for a single fluid Stokes jet and agree with Wang et al (2009).…”
Section: Linear Stability Analysismentioning
confidence: 99%
“…More complete linear stability studies of surfactant effects on CAF arrangements can be found in for quiescent fluids and Kwak, Fyrillas & Pozrikidis (2001) for liquid threads in extensional flow. The linear stability studies of surfactant-laden liquid threads by Hansen, Peters & Meijer (1999) and Timmermans & Lister (2002) are also of interest as well as the nonlinear models and calculations of Craster, Matar & Papageorgiou (2002).…”
Section: Introductionmentioning
confidence: 99%